Contribution of Vocational Interest and Self-Efficacy to the Work Readiness of Vocational School Students - Pramono, Ashar; Andi Muadz Palerangi (ILIN Institute Makassar, 2024)
The purpose of this study was to determine how the contribution of interest and self-efficacy to the work readiness of vocational students in Makassar city. This research method is quantitative, the data analysis techniques used are descriptive statistics, multiple linear regression prerequisite tests, and from the research conducted there is an influence of work interest and self-efficacy on the work readiness of vocational students. This is evidenced by the Sig value. The work interest variable is 0.041 < 0.05 probability and Sig value. The self-efficacy variable is 0.022 < 0.05 probability. It can be concluded that interest and self-efficacy contribute to the work readiness of vocational students.